Comparison of patient-reported outcomes between immediately and conventionally loaded mandibular two-implant overdentures: A preliminary study. Issue 3 (July 2016) - Omura, Yuri; Kanazawa, Manabu; Sato, Daisuke; Kasugai, Shohei; Minakuchi, Shunsuke
Abstract: Purpose: The aim of this preliminary study is to compare patient-reported outcomes between immediately and conventionally loaded mandibular two-implant overdentures retained by magnetic attachments. Methods: Nineteen participants with edentulous mandibles were randomly assigned into either an immediate loading group (immediate group) or a conventional loading group (conventional group). Each participant received 2 implants in the inter-foraminal region by means of flapless surgery. Prostheses in the immediate and conventional groups were loaded using magnetic attachments on the same day as implant placement or 3 months after surgery, respectively. All participants completed questionnaires (the Japanese version of the Oral Health Impact Profile for edentulous [OHIP-EDENT-J], the patient's denture assessment [PDA], and general satisfaction) before implant placement (baseline) and 1, 2, 3, 4, 5, 6, and 12 months after surgery. The median differences between baseline and each monthly score were compared using the Mann–Whitney U test. The differences in median and 95% confidence interval between two groups were analyzed. Results: The immediate group showed slightly lower OHIP-EDENT-J summary score at 1 and 3 months than the conventional group ( P  = 0.09). In the lower denture domain of PDA, the immediate group showed a statistically higher score at 3 months ( P  = 0.04). There was no statistically significant difference in general satisfaction between the two groups. Conclusions: Based on this preliminary study, immediate loading of mandibular two-implant overdentures with magnetic attachments tends to improve oral health-related quality of life and patient assessment earlier than observed with a conventional loading protocol.